TCS2 Increases Olaquindox-Induced Apoptosis by Upregulation of ROS Production and Downregulation of Autophagy in HEK293 Cells - Li, Daowen (Molecules, 2017)
Olaquindox, a feed additive, has drawn public attention due to its potential mutagenicity, genotoxicity, hepatoxicity and nephrotoxicity. The purpose of this study was to investigate the role of tuberous sclerosis complex (TSC2) pathways in olaquindox-induced autophagy in human embryonic kidney 293 (HEK293) cells. The results revealed that olaquindox treatment reduced the cell viability of HEK293 cells and downregulated the expression of TSC2 in a dose- and time-dependent manner. Meanwhile, olaquindox treatment markedly induced the production of reactive oxygen species (ROS), cascaded to autophagy, oxidative stress, and apoptotic cell death, which was effectively eliminated by the antioxidant N-acetylcysteine (NAC). Furthermore, overexpression of TSC2 attenuated olaquindox-induced autophagy in contrast to inducing the production of ROS, oxidative stress and apoptosis. Consistently, knockdown of TSC2 upregulated autophagy, and decreased olaquindox-induced cell apoptosis. In conclusion, our findings indicate that TSC2 partly participates in olaquindox-induced autophagy, oxidative stress and apoptosis, and demonstrate that TSC2 has a negative regulation role in olaquindox-induced autophagy in HEK293 cells.